2017
DOI: 10.3892/or.2017.5951
|View full text |Cite
|
Sign up to set email alerts
|

High pemetrexed sensitivity of docetaxel-resistant A549 cells is mediated by TP53 status and downregulated thymidylate synthase

Abstract: The chemoresistance of non-small cell lung cancer (NSCLC) that occurs in docetaxel (DOC) chemotherapy substantially decreases the survival of patients. To overcome DOC-induced chemoresistance, we established DOC-selected A549 lung cancer sublines (A549/D16 and A549/D32) and revealed that both sublines were cross-resistant to vincristine (VCR) and doxorubicin (DXR). Notably, both sublines were more sensitive to pemetrexed (PEM) than parental cells according to MTT and clonogenic assays. The expression levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…1A ). Similarly, cross resistance to anticancer drugs are reported in docetaxel-resistant 23 and gemcitabine-resistant A549 cells 24 . The detailed mechanism of acquisition of chemoresistance has not been fully understood.…”
Section: Discussionmentioning
confidence: 80%
“…1A ). Similarly, cross resistance to anticancer drugs are reported in docetaxel-resistant 23 and gemcitabine-resistant A549 cells 24 . The detailed mechanism of acquisition of chemoresistance has not been fully understood.…”
Section: Discussionmentioning
confidence: 80%
“…As a transcription factor, p53 induces the expression of downstream genes such as p21, BAX and GADD4 and plays an important role in cell apoptosis, cycle change, DNA repair, cell metabolism and autophagy [25] . Related studies have found that p53 gene polymorphism is associated with systemic lupus erythematosus susceptibility in Asian populations [26][27] . It has also been found that p53 induces the production of related proteins by binding to speci c DNA sequences, thereby inhibiting the expression of DNA methyltransferase gene, thereby affecting DNA methylation level [28] .…”
Section: Discussionmentioning
confidence: 92%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ for pemetrexed. Another study also revealed that the sensitivity of pemetrexed depends on the level of TS 18 . In A549 lung cancer cell line with downregulated TS level induced by docetaxel-resistance, pemetrexed sensitivity was increased compared to those parental cells, whereas it was decreased when exogenous TS was overexpressed in the docetaxel-resistant A549 cell line.…”
Section: Discussionmentioning
confidence: 94%